Treatment of acute postoperative endophthalmitis without hospital admission: do we dare? - Gurbaxani, A; Patel, C (2006)
INTRODUCTION: We report the successful management of a culture positive case of APE, without the need for hospital admission and discuss the merits of this strategy. CASE: A 79-year-old lady underwent uncomplicated cataract surgery in her left eye using phacoemulsification under topical and intracameral anaesthesia. She reported to eye casualty four days later, with pain and vision reduced to 6/60 in the left eye. A diagnosis of acute postoperative endophthalmitis was made. A vitreous biopsy was performed and antibiotics injected intravitreally on the same day. The patient was discharged on oral and topical antibiotics on the same day and reviewed subsequently in the clinic as an outpatient. Vision steadily improved and at one month following intravitreal injection her vision had improved to 6/9 unaided. The cornea remained clear, with a quiet anterior chamber and a clear view of the fundus. DISCUSSION: Current management of acute postoperative endophthalmitis in the UK includes a vitreous biopsy, administration of antibiotics into the vitreous cavity, admission of patients to a hospital ward and daily review. It is our opinion that under the circumstances where patients are fit and well, without significant co-morbidity, hospital admission is not necessary as demonstrated by the patient in our report.